Le postmodernisme doit supprimer la religion ? - Ćwiek, Przemysław Jan (Warszawskie Studia Teologiczne, 2017)
When John Paul II in the Encyclical „Fides et Ratio” wrote that „the tho-ught streams that refer to postmodernism deserve attention’ (point 91), this bro-ught about a lot of confusion among many philosophers. The nineties of the last century were marked by an intense confrontation of the widely understood Chri-stian philosophy with postmodernism. In postmodernism the destructive nihilism was perceived, and in many polemics more oen warned than encouraged to reflect on this philosophical stream.It has been some time since postmodernism was contentiously discussed and the term itself has ceased to evoke such strong emotions. The question worth arising is: whether philosophizing in the spirit of postmodernism must really ine-vitably lead to the rejection of religion as such?